Coupling of Ca(2+) microdomains to spatially and temporally distinct cellular responses by the tyrosine kinase Syk. - Ng, S; Nelson, C; Parekh, A (2009)
Communication between the cell surface and the nucleus is essential for regulated gene expression. In neurons, Ca(2+)-dependent gene transcription is sensitive to local Ca(2+) entry. In immune cells, excitation-transcription coupling is thought to involve global Ca(2+) signals. Here, we show that in mast cells, Ca(2+) microdomains from store-operated Ca(2+) release-activated Ca(2+) channels activate expression of the transcription factor c-fos. Local Ca(2+) entry is sensed by the tyrosine kinase Syk, which signals to the nucleus through the transcription factor STAT5. Ca(2+) microdomains also promote secretion of proinflammatory messengers, which, like gene expression, requires Syk. Syk therefore couples Ca(2+) microdomains to the activation of two spatially and temporally distinct cellular responses, revealing the versatility of local Ca(2+) signals in driving cell activation.